The Manipulation of Executive Stock Option Exercise Strategies: Information Timing and Backdating - CICERO, DAVID C. (Journal of Finance, 2009)
I identify three option exercise strategies executives engage in, including (i) exercising with cash and immediately selling the shares, (ii) exercising with cash and holding the shares, and (iii) delivering some shares to the company to cover the exercise costs and holding the remaining shares. Stock price patterns suggest executives manipulate option exercises. They use private information to increase the profitability of all three strategies, and likely backdated some exercise dates in the pre-Sarbanes-Oxley period to enhance the profitability of the latter two strategies, where the executive's company is the only counterparty. Backdating is associated with reporting of internal control weaknesses.